Produção de agentes coagulantes para clarificação da água a partir de taninos de espécies florestais da Caatinga - Anjos, Bruna Ferreira dos (2021)
The population increase in recent decades has been expressive, directly affecting the quality of life of the population, generating shortages in water distribution. In order to alleviate the impacts caused by chemical coagulants on water supply, studies have been carried out in order to generate alternatives for improving water distribution. One of these alternatives is the application of vegetable tannins. Thus, this research aimed to evaluate the potential of vegetable tannins extracted from forest species (Mimosa caesalpiniifolia, Anacardium occidentale, Pityrocarpa Moniliformis and Anadenanthera colubrina) as coagulating agents in water treatment. The content of tannins present in the bark and fruits of trees from a forest plantation, located in an experimental area at the Escola Agrícola de Jundiaí, municipality of Macaíba-RN, was analyzed. After collection, the skins and fruits were air-dried, ground and classified, the portion that went through a 16 mesh sieve and was retained in the 60 mesh sieve was used. For the extractions, three samples with 25g of dry material were used. The obtained extract was passed through a 150 mesh sieve, flannel fabric, filtered in a glass funnel and concentrated. Then, the total solids content (TST), Stiasny index (IS) and the condensed tannins content (TTC) were determined. The tannins obtained went through cationization, to later go through the water treatment process, using the jar-test equipment. Three types of concentration were used, 50mg/L1,100mg/L1 and 150mg/L1, pH and turbidity were initially measured in each test. It was possible to observe that A. occidentale presented a better efficiency when coagulating, when compared to the other species, with removal of turbidity from 99% of the treated water, a value not found in the literature with forest species from the Caatinga, being one of the pioneering researches in its use. of cashew husk for water treatment.